Clinical Relevance of Autoantibodies in Patients with Autoimmune Bullous Dermatosis - Lilla Mihályi; Mária Kiss; Attila Dobozy; Lajos Kemény; Sándor Husz (Clinical and Developmental Immunology)
The authors present their experience related to the diagnosis, treatment, and followup of 431 patients with bullous pemphigoid, 14 patients with juvenile bullous pemphigoid, and 273 patients with pemphigus. The detection of autoantibodies plays an outstanding role in the diagnosis and differential diagnosis. Paraneoplastic pemphigoid is suggested to be a distinct entity from the group of bullous pemphigoid in view of the linear C3 deposits along the basement membrane of the perilesional skin and the “ladder” configuration of autoantibodies demonstrated by western blot analysis. It is proposed that IgA pemphigoid should be differentiated from the linear IgA dermatoses. Immunosuppressive therapy is recommended in which the maintenance dose of corticosteroid is administered every second day, thereby reducing the side effects of the corticosteroids. Following the detection of IgA antibodies (IgA pemphigoid, linear IgA bullous dermatosis, and IgA pemphigus), diamino diphenyl sulfone (dapsone) therapy is preferred alone or in combination. The clinical relevance of autoantibodies in patients with autoimmune bullous dermatosis is stressed.